Release of retromalleolar flexor retinaculum and combined flexor digitorum longus and flexor hallucis longus Z-plasty in checkrein deformity: a case report - Irianto, Komang Agung; Leonarto, Enrico; Handoyo, Henry Ricardo (Universa Medicina, 2023)
BackgroundCheckrein deformity is a rare abnormality comprising flexor hallucis longus (FHL) tendon entrapment in the posterior foot due to post-traumatic or ischemic retraction of the FHLtendon following soft tissue trauma. The diagnosis is essentially clinical, but complemented by imaging to rule out unrecognized causes and evaluate the fracture healing process. This case report is the first Indonesian study to describe release of the flexor retinaculum and Z-plasty (lengthening) of flexor digitorum longus (FDL) and FHL tendons through a medial retromalleolar approach to repair the deformity. Case DescriptionWe present the case of a 51-year-old male who complained of clawing of his right first and second toes. The interest of this study lies in the fact that this patient had never experienced ankle or distal tibial fractures, only a trivial injury two years back when the patient kicked a stone at work and had a bruise on his right second toe with no fracture. Exploration of FHL tendons was performed at the level of the midfoot. The patient was planned for surgery with a medial retromalleolar ankle approach, which facilitates the release of the flexor retinaculum, in conjunction with a Z-tenotomy on the FHL and FDL tendons. ConclusionA correction was achieved, and two months post-surgery there were no recurrences of the deformity. However, this surgical procedure requires more cases to support an evaluation of its effectiveness. We suggest that exploration at the ankle and midfoot should be the primary surgical intervention in similar cases of checkrein deformity.